Switching Equipment - Ito, Hiroki; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This CIGRE Green Book provides the entire know-how about switches in a high voltage system. The switching equipment includes circuit breakers, vacuum interrupters, disconnecting switches, and earthing switches used in AC & DC transmission and distribution systems. The Green book describes different switching equipments and their roles in the power systems. It explains the fundamental switching behaviors in power systems targeted for practitioners and students and joining electrical industries. The Green book also covers fundamental specific subjects including DC circuit breakers, controlled switching, fault current limiting devices and future technologies. Like all Green books, this book covers the cumulative understanding of numerous experts in the CIGRE study committee. It offers the approved and outstanding practical knowledge of CIGRE Study committee A3 and was collected by Dr. Hiroki Ito.
Chapter 1: Study Committee A3 activity -- Chapter 2: Switching Equipment in Power systems -- Chapter 3: Interrupting phenomena -- Chapter 4: Switching Phenomena in Power systems -- Chapter 5: Circuit Breakers (Oil breaker, Air-blast breaker, Gas circuit breaker, VCB, GMCB) -- Chapter 6: AC Disconnecting switches and Earthing switches -- Chapter 7: Fault Current Limiters -- Chapter 8: Controlled switching -- Chapter 9: HVDC switching equipment -- Chapter 10: Novel technologies.
Keywords: Electric power production; Electrical Power Engineering; Mechanical Power Engineering